Efektivitas Pelatihan Psychological Capital Untuk Mengurangi Teacher Burnout Pada Guru SMK - Yasmin Adlina Heraputri Utami; Qonita Hasna'ul Azizah; Frikson Christian Sinambela (Jurnal Ilmiah Psikologi MIND SET, 2022)
Over the course of COVID-19 pandemic, teachers were given lots of new tasks to adapt and prepare long distance learning programs for their students. Those conditions pose risks to the teacher's physical and mental state. This paper showed that some teachers at X Vocational School in Surabaya experience teacher burnout. Burnout is a very common occurrence in individuals who work in the service industry, including teachers. 14 Vocational School teachers who showed medium to high levels of teacher burnout were treated with psychological capital training to reduce the burnout level. Teachers were trained to develop and apply four aspects of psychological capital; hope, efficacy, resilience, and optimism (HERO) in six training sessions. This research showed negative correlation between psychological capital with teacher burnout (r=-0.958**), there was a significant difference between teacher burnout before and after treatment (p=0.001), but there was no significant difference between psychological capital before and after treatment (p=0.417). This research concluded that even though some teachers have good psychological capital levels, they still need to be trained to develop and apply it to prevent teacher burnout.